Giant bypass aneurysm, a cause of suspected cardiac mass - Sohns, Jan M (Springer International Publishing, 2014)
INTRODUCTION: A 66-years old man suffering from coronary artery disease appeared without symptoms for routine follow-up in our clinic. CASE DESCRIPTION: The echocardiogram revealed a tumorous mass of the right atrium and right ventricle. In the past, coronary revascularization with venous grafts of the right coronary artery and circumflex artery as well as internal mammaria graft to the left anterior descending artery was performed 20 years before. The general clinicians presented the case to the surgeons and it was decided to perform cardiac MRI as a preoperative diagnostic modality. DISCUSSION AND EVALUATION: Following cardiac magnetic resonance imaging (MRI) showed a mass in the pericardium in the right atrioventricular groove with thrombotic material. Due to the MRI the patient underwent coronary angiography to confirm an aneurysm. CONCLUSIONS: The learning points from this case are that cardiac MRI is a very useful tool for further evaluation of suspected cardiac masses and should be performed for further characterization.